Effects of progressive burial on matrix porosity and permeability of dolostones in the foreland basin of the Alpine Orogen, Switzerland. (February 2019) - Aschwanden, Lukas; Diamond, Larryn W.; Adams, Arthur
Abstract: The changes in rock-matrix porosity and permeability that carbonate reservoirs undergo with increasing burial depth are poorly understood. This lack of understanding raises the risks involved in exploring and engineering deep reservoirs for geo-energy applications. To provide more insight into compaction processes, the present study examines the effects of progressive burial on two dolomitized mudstone units belonging to the Middle Triassic Muschelkalk within the Swiss Molasse Basin, situated in the foreland of the Alpine Orogen. Based on investigations of wireline logs and drill cores retrieved from up to 5000 m depth, we report the burial modification of crystal textures, pore sizes, pore geometries and their impact on matrix porosity and permeability. Within the first 1500 m below surface, porosity is found to drop from 40±2 to 18±1 vol% and permeability drops from 105±15 to ∼1 mD. At depths >3000 m, porosity and permeability maintain nearly constant values of 6±2 vol% and <0.01 mD, respectively. These trends are due to the cumulative effects of a series of partly concurrent processes: at depths <1200–1900 m, mechanical rotation and fracturing of the euhedral dolomite crystals promotes closer packing and constitutes the dominant porosity-reducing mechanism; at depths >1900 m, mechanical compaction is inactive and pressure solution at crystal contacts and along stylolites (both diagenetic and tectonic), without any associated cementation, accounts for porosity loss. At depths >3000 m, collapse of pores by pressure solution is compounded by pore-clogging by hydrothermal dolomite introduced by external fluids. Throughout the entire depth range, stylolitization incrementally thins the formations, however, the dissolved material is not locally reprecipitated. Highlights: Compaction trends in mud-dominated dolostones are exponential. Loss of 32–43 vol% matrix porosity upon 3000 m of burial. Matrix permeability decreases by a factor of 10 4 upon 3000 m of burial. Progressive changes in crystal textures, pore sizes and pore geometry with burial. Deep diagenetic cementation deviates the compaction trends.